2016
DOI: 10.1371/journal.pone.0150784
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Localization of Citrullinated Proteoglycan Aggrecan in Human Articular Cartilage

Abstract: BackgroundRheumatoid arthritis (RA) is an autoimmune disease of the synovial joints. The autoimmune character of RA is underscored by prominent production of autoantibodies such as those against IgG (rheumatoid factor), and a broad array of joint tissue-specific and other endogenous citrullinated proteins. Anti-citrullinated protein antibodies (ACPA) can be detected in the sera and synovial fluids of RA patients and ACPA seropositivity is one of the diagnostic criteria of RA. Studies have demonstrated that RA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Previous studies have reported immunogenic aggrecan peptides and demonstrated responses to citrullinated aggrecan in samples from patients with RA . To corroborate the relevance of citrullinated aggrecan epitope–specific T cells, we compared the frequency of T cells specific for Cit‐aggrecan 225 and Cit‐aggrecan 553 in RA patients and healthy controls with DRB1*04:01 haplotypes.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Previous studies have reported immunogenic aggrecan peptides and demonstrated responses to citrullinated aggrecan in samples from patients with RA . To corroborate the relevance of citrullinated aggrecan epitope–specific T cells, we compared the frequency of T cells specific for Cit‐aggrecan 225 and Cit‐aggrecan 553 in RA patients and healthy controls with DRB1*04:01 haplotypes.…”
Section: Resultsmentioning
confidence: 95%
“…IgM depletion was verified by anti‐IgM Western blotting. For enzyme‐linked immunosorbent assay (ELISA), wells of 96‐well ELISA plates (Nunc) were coated overnight with recombinant human aggrecan G1 or citrullinated recombinant human aggrecan G1 domain (0.2 μg/well each) in 100 μl/well of 0.15 M sodium carbonate buffer (pH 9.6) at room temperature . Unbound antigen was removed by washing with horseradish peroxidase (HRP) wash buffer (Inova Diagnostics).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In RA, multiple proteins are citrullinated, especially in target organs of the disease, primarily the synovium but also in the lungs (20) and in myocardial tissue (21). In the RA joints, citrullinated fibrin is not only particularly abundant (22) but also several other citrullinated proteins including vimentin and aggrecan (23) are detectable. Citrullination is not an RA-specific process, and citrullinated proteins are present in several other inflammatory processes including the inflamed skeletal muscle tissue in myositis (24) and the synovium of spondyloarthritis patients (25).…”
Section: Neutrophils Citrullination and Netosis In Ramentioning
confidence: 99%